Should Network Structure Matter in Agent-Based Finance? - Simone Alfarano; Mishael Milaković (Kiel University, Department of Economics, 2008)
We derive microscopic foundations for a well-known probabilistic herding model in the agent-based finance literature. Lo and behold, the model is quite robust with respect to behavioral heterogeneity, yet structural heterogeneity, in the sense of an underlying network structure that describes the very feasibility of agent interaction, has a crucial and non-trivial impact on the macroscopic properties of the model.
Keywords: 330; Herding; networks; mean-field approach; N-dependence; Börsenkurs; Finanzmarkt; Mikrostrukturanalyse; Agent-based Model; Business Network; Herdenverhalten; Theorie